“Medida da suavidade da mobilidade funcional por meio do comprimento do arco espectral (SPARC) e sua utilidade para a avaliação de quedas em idosos longevos” - Figueiredo, Anelise Ineu (2021)
Introduction: The aging-related neuromuscular and cognitive decline can lead to less smooth movements and motor transitions, with an impact on functional mobility. The analysis of functional mobility is important to diagnose and monitor impairments resulted from physical and cognitive declines that impact human gait. Quantitative measures of movement smoothness could be fundamental when performing the assessment of functional mobility based on the instrumented Timed Up and Go (iTUG) test. For this, we used a linear and angular spectral arc length (SPARC) analysis in the iTUG. Objective: The aim of this research was to study whether the smoothness of functional mobility assessed by the SPARC measures in the iTUG is a useful measure to detect the occurrence of falls in oldest-old. Method: This is a casecontrol study. The sample consisted of 64 oldest-old who underwent the following tests: initial anamnesis questionnaire, Mini Mental State Examination, assessment of the presence of depressive symptoms, levels of physical activity, concern about falling, confidence in balance during daily living activities, performance in static balance test and iTUG for the evaluation of the classic metrics of the test and SPARC. Results: Our results demonstrate that, in our first study (Study 1), the SPARC was able to distinguish oldest-old fallers and non-fallers during the iTUG test. Furthermore, we observed that the turning moments during the iTUG induced less smooth movements, which was more pronounced in the oldest-old fallers. In our second study (Study 2), we observed that the combination of SPARC metrics and the duration of the simple iTUG increases the ability to predict falls in oldest-old. In short, we concluded that the evaluation of SPARC metrics add value to the iTUG test and can contribute to the assessment of the tendency for the occurrence of falls in oldestold living in the community.